Hydatidosis in Slaughtered Livestock in Al-Qubbah City –Libya - Saleh, Wafaa; Elmahjoob, Mabrouka (Journal of Pure & Applied Sciences, 2024)
Hydatidosis is one of the most common zoonotic diseases worldwide including in Libya. It leadsto health problems and economic losses for human and animals. This study was conducted in Alqubbah city and the data of slaughtered animals and the infected ones were obtained by using data forms and interviews with the city abattoir workers. (102) cysts isolated from different organs of an infected animalswere examined to determine the fertility by emptying the hydatid fluids and examining these fluids for the presence of protoscoleces, the viability was determined by staining the scoleces with 0.1% eosin aqueous solution. The results of the study showed that the prevalence rate of hydatid cysts among slaughtered animals was 4.3%. Sheep, females and older animals were the most affected groups. Fertility and viability rates were 49% and 69.4% respectively. Cysts isolated from sheep, hepatic cysts and large cysts had the highest fertility and viability rates. to conclude that sheep play an important role in transmission and continuance of the hydatid cysts infection in the region, whereas they were the most slaughtered and consumed by residents, the hydatid cysts infection in sheep was higher in comparison to the other species and fertility and viability rates were high in cysts isolated from the sheep.